VD_FINDINFO HC / 2013 / 440 vom 30. Juli 2013 - VD Tribunal cantonal (2013)
OBLIGATION D'ENTRETIEN, FRAISEN GÉNÉRAL, REVENU, REVENU ACCESSOIRE, ENFANT, CONCUBINAGE, MINIMUM VITAL | 163 CC, 176 CC, 179 CC